Optimal incentive regulation of multinational enterprises - Giacomo Calzolari (Fondazione Eni Enrico Mattei (FEEM), 1999)
Multinational enterprises (MNEs) have started to populate also regulated sectors. Their linked international activities and credible threats to relocate are then new concerns for regulators. We study a multiprincipal model in which a privately informed MNE (the agent) produces for two countries and is regulated by the two national authorities (the principals). We show that standard theory in the economics of regulation must be reconsidered in a world with MNEs and novel results arise. We study MNE's incentives to allocate resources to lobby the two non-benevolent regulators and we analyse optimal ownership patterns as a substitute for co-operation in regulation between countries.
Keywords: L51; F23; 330; Multinational enterprises; Regulation; Asymmetric information; Multiprincipal; Lobbying; Anreizregulierung; Multinationales Unternehmen; Prinzipal-Agent-Theorie; Asymmetrische Information; Interessenpolitik; Spieltheorie; Theorie